The Influence of Religiosity and Profit Margin on Increasing the Quantity of Customers in Sharia Bank - Hadiyan, Edwin; Anwar, Saeful; Maknuun, Lu’lu’ Il; Enggal, Dwi; Fahmi, Ahmad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study aims to ascertain the impact of religiosity and profit margin on the augmentation of customer quantity in private banks, both partially and simultaneusly. The employed research methodology was quantitative, utilizing a sample size of 183 respondents. The research findings, processed using the SPSS program, indicate that the customer quantity is indeed influenced by both religiosity and profit margin the first hypothesis, which aimed to investigate the impact of religiosity on the level of customer quantity development, yielded an R value of 0,169, indicating quite significant result. The second hypothesis, which aimed to examine the impact of porfit margin on the level of customer quantity development of customer quantity, yielded a value of 0,184, also indicating quite significant result. Lastly, the third hypothesis, which aimed to explore the combined influence of religiosity and profit margin on the level of customer quantity development, yielded a value of 0,193, again indicating quite significant result.